2007
DOI: 10.1111/j.1365-2427.2007.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Eulittoral macroinvertebrate communities of lowland lakes: discrimination among trophic states

Abstract: 1. Nutrient inputs from urban and agricultural land use often result in shifts in species composition of pelagic and profundal invertebrate communities. Here, we test if nutrient enrichment affects the composition of eulittoral macroinvertebrate communities, and, if so, if macroinvertebrate communities of five different habitat types reflect differences in trophic state. 2. Macroinvertebrate community composition of 36 lakes was significantly correlated with total phosphorus (TP) concentration, the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 40 publications
8
63
0
Order By: Relevance
“…Xylophages recorded in other studies were represented in lakes by the caddisfly genus Lype sp. (Psychomyiidae) (Brauns et al, 2007(Brauns et al, , 2011 and wood-mining chironomids: Glyptotendipes sp. and Dicrotendipes sp.…”
Section: Effects Of Cwd On Habitat Heterogeneitymentioning
confidence: 99%
“…Xylophages recorded in other studies were represented in lakes by the caddisfly genus Lype sp. (Psychomyiidae) (Brauns et al, 2007(Brauns et al, , 2011 and wood-mining chironomids: Glyptotendipes sp. and Dicrotendipes sp.…”
Section: Effects Of Cwd On Habitat Heterogeneitymentioning
confidence: 99%
“…Increased levels of eutrophication are often accompanied by a decline in macroinvertebrate diversity (Donohue et al 2009), an increase in density, and a decrease in wet biomass (mollusks with shells) (Crowns et al 1992, Wollheim and Lovvorn 1995, Gong and Xie 2001, Xiong et al 2003. However, most previous research has been restricted to local-scale studies, i.e., in a single lake or in a few lakes (Saether 1980, Kerovec et al 1989, Gong et al 2000, Xiong et al 2003, Timm et al 2006, and few studies have covered a complete range of nutrient concentrations (Brauns et al 2007a, Donohue et al 2009). …”
mentioning
confidence: 99%
“…Brauns et al (2007) observed that while a community part was related to organic matter and conductivity reduction, there was another positively related to phosphorous. For these authors, the relation with phosphorous infers about productivity and, therefore, the macroinvertebrate's composition was associated to system productivity.…”
Section: Discussionmentioning
confidence: 97%
“…When entering in the metropolitan Curitiba's region, the riverbed was modified, providing extension and depth, in many points it remakes the riverbed or cut the natural one, transforming the meanders in to horseshoe lakes. Brauns et al (2007) argue that while domestic and industrial discharges have been reduced in recent years, due to wastewater treatment, the lakes still receive nitrogen from urban areas, and phosphorous from agricultural waste, besides atmospheric deposition. According to Vollenweider (1968) the increase of nutrients, particularly phosphorus, enriches the environment and favors the algal blooms, which can reduce the development of submerged plants (Chandra et al 2005).…”
Section: Introductionmentioning
confidence: 99%